Association of Arterial Metabolic Content with Cerebral Blood Flow Regulation and Cerebral Energy Metabolism–A Multimodality Analysis in Aneurysmal Subarachnoid Hemorrhage. (November 2022) - Svedung Wettervik, Teodor; Hånell, Anders; Howells, Timothy; Ronne-Engström, Elisabeth; Enblad, Per; Lewén, Anders
Background: In this study, the association of the arterial content of oxygen, carbon dioxide, glucose, and lactate with cerebral pressure reactivity, energy metabolism and clinical outcome after aneurysmal subarachnoid hemorrhage (aSAH) was investigated. Methods: In this retrospective study, 60 patients with aSAH, treated at the neurointensive care (NIC), Uppsala University Hospital, Sweden, between 2016 and 2021 with arterial blood gas (ABG), intracranial pressure, and cerebral microdialysis (MD) monitoring were included. The first 10 days were divided into an early phase (day 1 to 3) and a vasospasm phase (day 4 to 10). Results: Higher arterial lactate was independently associated with higher/worse pressure reactivity index (PRx) in the early phase (β = 0.32, P = .02), whereas higher pO2 had the opposite association in the vasospasm phase (β = −0.30, P = .04). Arterial glucose and pCO2 were not associated with PRx. Higher arterial lactate (β = 0.29, P = .05) was independently associated with higher MD-glucose in the vasospasm phase, whereas higher pO2 had the opposite association in the vasospasm phase (β = −0.33, P = .03). Arterial glucose and pCO2 were not associated with MD-glucose. Higher pCO2 in the early phase, lower arterial glucose in both phases, and lower arterial lactate in the vasospasm phase were associated ( P < .05) with better clinical outcome. Conclusions: Arterial variables associated with more vasoconstriction (higher pO2 and lower arterial lactate) were associated with better cerebral pressure reactivity, but worse energy metabolism. In severe aSAH, when cerebral large-vessel vasospasm with exhausted distal vasodilation is common, more vasoconstriction could increase distal vasodilatory reserve and pressure reactivity, but also reduce cerebral blood flow and metabolic supply. The MD may be useful to monitor the net effects on cerebral metabolism in PRx-targeted NIC.